Juridical Review Oo The Effectiveness of The Motor Vehicle Tax Receivables Collection Program in Semarang City - Agung Prasetyo, Raden Soeko; Kadi Sukarna; Muhammad Junaidi; Kukuh Sudarmanto; Endah Pujiastuti (Universitas Semarang, 2025)
The purpose of this study is to determine and analyze the effectiveness of the motor vehicle tax receivables collection program in Semarang City, as well as to determine and analyze the supporting and inhibiting factors for the effectiveness of the program. This research is a type of empirical juridical legal research with a statutory approach. The research specification uses descriptive analysis. The data in this study were obtained through interviews and literature studies and then analyzed qualitatively. The results of the study explain that the effectiveness of the motor vehicle tax receivables collection program in Semarang City is marked by an increase in motor vehicle tax revenue compared to the same month period last year and a significant increase in revenue before the program was implemented. Supporting factors for the effectiveness of the motor vehicle tax receivables collection program in Semarang City are cooperation with other agencies and optimizing the use of technology, inhibiting factors are a lack of public awareness and technical obstacles such as data differences between motor vehicle data and vehicle owners. It is hoped that in the future, the collection program for motor vehicle tax receivables in Semarang City can continue to be improved by improving the data collection system for vehicles and vehicle owners to be more accurate, and increasing socialization to the public about the importance of paying taxes on time. In addition, increased coordination between related agencies is also expected to minimize technical obstacles that have been a hindrance. Thus, it is expected that motor vehicle tax revenue will be more optimal, and this program can run more effectively and efficiently.